Soy-based infant nutrition: a review - Yvan Vandenplas; Badriul Hegar (Paediatrica Indonesiana, 2014)
Dietary consumption of soy varies worldwide. In Asia, people traditionally consume large quantities of soy, while in Europe, soy is not part of the traditional or daily eating habits. The USA is a major soy producer. The mean intake of isoflavones by an adult is 8 - 50 mg/day in Asia but only 0.5 - 3.5 mg/day in the Western world.1 The soy intake of a vegetarian is 3 - 12 mg/day and a vegan achieves an intake of 15-60 mg/day.2 In the early 1900s, soy-protein preparations were the only option for the treatment of cow's milk protein allergy (CMPA) . The first report of the use of a soybean -based formula for infants dates from 1909.3 Most soy drinks are not enriched with zinc, iron, calcium, phosphorous, methionine, or carnitine. Soy drinks also do not contain soy isolate. Soy products that do not fulfill the criteria to be an infant formula are not adapted for infant feeding.